Redescriptions and taxonomic notes on species of the Synalpheus townsendi Coutiere, 1909 complex (Decapoda: Caridea: Alpheidae) - Salazar, Margarita Hermoso; Wicksten, Mary; Morrone, Juan J. (Zootaxa, 2005)
We compared morphological features in 122 specimens of the Synalpheus townsendi species complex from the Caribbean, Gulf of Mexico and eastern Pacific. Our objectives were to examine the taxonomy of S. townsendi townsendi, S. t. mexicanus, S. t. brevispinis and S. t. peruvianus, which we felt have not been appropriately described and to reconsider their status. Based on examination of type material and different characters, we conclude that these taxa should be treated as distinct species, S. townsendi Coutière, 1909; S. mexicanus Coutière, 1909, S. brevispinis Coutière, 1909 and S. peruvianus Rathbun, 1910. We agree with Dardeau, 1986, that S. scaphoceris Coutière, 1910, is a distinct species. Specimens identified as S. townsendi productus Coutière, 1909, overlap in morphology with typical S. townsendi, and therefore are not considered to warrant designation as a separate taxon. Synalpheus mexicanus is not endemic to the Gulf of California.